High-Speed Current dq PI Controller for Vector Controlled PMSM Drive. (24th December 2013) - Marufuzzaman, Mohammad; Reaz, Mamun Bin Ibne; Rahman, Labonnah Farzana; Chang, Tae Gyu
Abstract : High-speed current controller for vector controlled permanent magnet synchronous motor (PMSM) is presented. The controller is developed based on modular design for faster calculation and uses fixed-point proportional-integral (PI) method for improved accuracy. Current d q controller is usually implemented in digital signal processor (DSP) based computer. However, DSP based solutions are reaching their physical limits, which are few microseconds. Besides, digital solutions suffer from high implementation cost. In this research, the overall controller is realizing in field programmable gate array (FPGA). FPGA implementation of the overall controlling algorithm will certainly trim down the execution time significantly to guarantee the steadiness of the motor. Agilent 16821A Logic Analyzer is employed to validate the result of the implemented design in FPGA. Experimental results indicate that the proposed current d q PI controller needs only 50 ns of execution time in 40 MHz clock, which is the lowest computational cycle for the era.